Large subglacial source of mercury from the southwestern margin of the Greenland Ice Sheet - Hawkings, Jon R.; Linhoff, Benjamin S.; Wadham, Jemma L.; Stibal, Marek; Lamborg, Carl H.; Carling, Gregory T.; Lamarche-Gagnon, Guillaume; Kohler, Tyler J.; Ward, Rachael; Hendry, Katharine R.; Falteisek, Lukáš; Kellerman, Anne M.; et al. (Nature Geoscience, 2021)
The Greenland Ice Sheet is currently not accounted for in Arctic mercury budgets, despite large and increasing annual runoff to the ocean and the socio-economic concerns of high mercury levels in Arctic organisms. Here we present concentrations of mercury in meltwaters from three glacial catchments on the southwestern margin of the Greenland Ice Sheet and evaluate the export of mercury to downstream fjords based on samples collected during summer ablation seasons. We show that concentrations of dissolved mercury are among the highest recorded in natural waters and mercury yields from these glacial catchments (521–3,300 mmol km −2 year −1 ) are two orders of magnitude higher than from Arctic rivers (4–20 mmol km −2 year −1 ). Fluxes of dissolved mercury from the southwestern region of Greenland are estimated to be globally significant (15.4–212 kmol year −1 ), accounting for about 10% of the estimated global riverine flux, and include export of bioaccumulating methylmercury (0.31–1.97 kmol year −1 ). High dissolved mercury concentrations (~20 pM inorganic mercury and ~2 pM methylmercury) were found to persist across salinity gradients of fjords. Mean particulate mercury concentrations were among the highest recorded in the literature (~51,000 pM), and dissolved mercury concentrations in runoff exceed reported surface snow and ice values. These results suggest a geological source of mercury at the ice sheet bed. The high concentrations of mercury and its large export to the downstream fjords have important implications for Arctic ecosystems, highlighting an urgent need to better understand mercury dynamics in ice sheet runoff under global warming.